2017
DOI: 10.1590/1413-70542017413002317
|View full text |Cite
|
Sign up to set email alerts
|

Egg quality assessment at different storage conditions, seasons and laying hen strains

Abstract: Eggs are one of nearly perfect protein foods, offering nutrients of great biological value. However, during storage, egg albumen and yolk components may alter and deteriorate egg quality. Therefore, the aim of this work was to assess egg quality during 9-week storage. Parameters such as Haugh unit, weight loss, egg width and length, specific gravity, yolk and albumen dimensions and their pH were evaluated weekly. A total of 270 eggs (n=5) collected from two different hen strains were evaluated under room (20 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
67
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 16 publications
10
67
2
10
Order By: Relevance
“…Şamlı et al [26] study determined that the egg yolk index was 44.09 in fresh eggs; 40.77 (5°C ) and 32.73 (29°C ) at the end of 10 days. In our study, it was seen that the value of fridge group egg yolk index obtained from day 28 was compatible with the value taken from Şamlı et al 's [30] fridge group (5°C ) on 10 th day.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Şamlı et al [26] study determined that the egg yolk index was 44.09 in fresh eggs; 40.77 (5°C ) and 32.73 (29°C ) at the end of 10 days. In our study, it was seen that the value of fridge group egg yolk index obtained from day 28 was compatible with the value taken from Şamlı et al 's [30] fridge group (5°C ) on 10 th day.…”
Section: Discussionsupporting
confidence: 90%
“…In the study of Feddern et al [30] the HU value decreased from 95.75 to 88.19 in the eggs they kept in the cold chain (0-5°C ) for 3 weeks, whereas in the warm environments (20-30°C ) the values were reduced from 98.60 to 51.92. According to our research results, HU values were found to be statistically significant between the groups kept at fridge versus at room temperature (P<0.05).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Albumen height and Haugh unit values tend to decrease during storage, which concurs with the findings of Feddern et al (2017). According to egg quality grades of USDA (2000) manual, a higher HU means higher egg quality.…”
Section: Discussionsupporting
confidence: 86%
“…Because of that, increasing the storage time and temperature affected YI and YI might be a indicator of deterioration. Feddern et al (2017) reported that YI has to be between 0.39 and 0.45. The current results showed that YI values of eggs stored at room temperatures for two and three weeks are lower than 0.39.…”
Section: Discussionmentioning
confidence: 99%